Talking-associated cognitive loads degrade the quality of gaze behavior - Takuya Suzuki; Takaji Suzuki; Shintaro Uehara (PLoS ONE, 2025)
Talking-associated cognitive distractions have been known to significantly impact physical reactions in response to visual information, leading to an increased crash risk while driving. The visuomotor processes required for driving include gaze behavior, cognitive processes, and responsive physical actions. However, how talking-associated cognitive loads affect the quality of gaze behavior remains unclear. Healthy participants performed center-out eye movements toward a peripheral visual target as quickly and accurately as possible under three different conditions: while verbally communicating (talking), listening to audio clips, or performing nothing other than the eye movement task. We found delays in the time needed to react to, move to, and fixate on a peripherally presented visual target in the talking condition compared with the other two conditions. Our results demonstrate that talking-associated cognitive loads are likely to have a strong enough impact to interfere with neural processes for initiating and controlling eye movement. These findings suggest that delayed physical responses and/or impairments in driving performance under cognitively demanding situations may partly result from delayed visual responses to surrounding events, followed by less accurate eye movement control when directing to and maintaining fixation on those stimuli.